PERFORMA NEUTRONIK BAHAN BAKAR LiF-BeF2-ThF4-UF4 PADA SMALL MOBILE-MOLTEN SALT REACTOR - Rokhman, S.N.; Widiharto, Andang; Kusnanto (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
The analysis of neutronic performance has been carried out for the molten salt fuel LiF-BeF2-ThF4-UF4 on a Small Mobile-Molten Salt Reactor (SM-SMR). The core configurations and operating temperature should be adjusted in using the new fuel in order to get the calculated keff and CR (conversion ratio) are > 1 in the fraction of 0.5% 233U, 20% 232Th, 28% Li, 51.5% Be. After obtained that keff and CR close to 1, then the analysis of changes in the Th to Be and Be to Li are carried out, it indicates the changes of keff and CR. Then the 233U fraction is varied between 0.5–0.46% to obtain the condition keff > 1 and CR > 1. To determine the temperature coefficient of reactivity (αT),the temperature of core is changed about +25K dan +50K. To determine the void reactivity coefficient (αV), fuel density is reduced to 90%. The result shows that the reduction of Th causes the decrease of CR and increase of keff due to the number fertile material is less. The addition of Be to Li will make the keff is increase and the CR is decrease, because the macroscopic absorption cross section of Li is greater than Be. From the five 233U composition in the ranges 0.5–0.46%, the calculated keff and CR varies in the range of 1.00001 – 1.00327 and 1.00016 – 1.00731, respectively. For power peaking factor (PPF), the calculation results give the value in the range of 2.4311 - 2.4714. However, for the safety parameters, the negative temperature reactivity coefficient (αT) and negative void reactivity CR (αV) in the range of 4.972×10-5 – 5.909×10-5 and 2.596×10-2 - 2,8287×10-2 ∆k/k/K, respectively. It can be concluded that the SM-MSR core has negative value for those reactivity for all fractions, so the core fulfill the safety criteria and inherent safety.